2023
DOI: 10.1038/s41467-023-38981-w
|View full text |Cite
|
Sign up to set email alerts
|

Global warming accelerates soil heterotrophic respiration

Abstract: Carbon efflux from soils is the largest terrestrial carbon source to the atmosphere, yet it is still one of the most uncertain fluxes in the Earth’s carbon budget. A dominant component of this flux is heterotrophic respiration, influenced by several environmental factors, most notably soil temperature and moisture. Here, we develop a mechanistic model from micro to global scale to explore how changes in soil water content and temperature affect soil heterotrophic respiration. Simulations, laboratory measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 65 publications
0
7
1
Order By: Relevance
“…High temperatures can increase respiration and reduce biomass gains from elevated CO 2 (Baker et al., 2000; Timlin et al., 2006). Increased temperatures are also expected to increase efflux of carbon from soils because of increased respiration and reduction of soil water (Nissan et al., 2023). There is evidence (Cox et al., 2020) that nighttime temperatures are increasing faster than daytime, so the diurnal temperature differentials are higher and this differential can be more important than the temperatures themselves (Yang et al., 2023).…”
Section: Development Of Crop Modelsmentioning
confidence: 99%
“…High temperatures can increase respiration and reduce biomass gains from elevated CO 2 (Baker et al., 2000; Timlin et al., 2006). Increased temperatures are also expected to increase efflux of carbon from soils because of increased respiration and reduction of soil water (Nissan et al., 2023). There is evidence (Cox et al., 2020) that nighttime temperatures are increasing faster than daytime, so the diurnal temperature differentials are higher and this differential can be more important than the temperatures themselves (Yang et al., 2023).…”
Section: Development Of Crop Modelsmentioning
confidence: 99%
“…For example, soil warming can induce modifications in microbial activity, facilitating thermal adaptation and influencing SOC decomposition rates, ultimately impacting Rs (Bradford et al., 2008). Several meta‐analyses have synthesized warming experiments (see below), but substantial uncertainty remains about the in situ Rs response to temperature changes (Nissan et al., 2023). Novel experiments have challenged conventional wisdom on the importance and vulnerability to warming of deeper soil horizons (Hanson et al., 2017; Hicks Pries et al., 2017; Soong et al., 2021; Q. Zhang et al., 2023a).…”
Section: In Situ Measurements and Manipulationsmentioning
confidence: 99%
“…In spite of this demonstrated importance of Rs, its underlying processes remain highly uncertain components of Earth System Models (Varney et al., 2022), and ecosystem respiration more generally dominates the uncertainty of terrestrial carbon storage in CMIP6 models (Wei et al., 2022). The interaction between Rs and environmental change thus remains one of the greatest sources of uncertainty in climate and earth system projections (Nissan et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, environmental factors and sediment properties (moisture content, pH) could be the main factors affecting the sediment nitrogen distribution [32]. Furthermore, the physicochemical properties of sediment (particularly the moisture content) can affect microbial heterotrophic respiration and thus affect the sediment carbon fluxes [34,35].…”
Section: Carbon-nitrogen Coupling In Constructed Wetland Sedimentsmentioning
confidence: 99%
“…Some studies have indicated that the vegetation composition and plant carbon inputs of wetlands are direct factors affecting sediment carbon distribution [20,31], while climate and sediment properties (water content, pH, and bioavailable carbon) are the main factors affecting sediment nitrogen distribution [32]. However, it has also been shown that changes in vegetation can affect the composition of microbial communities relevant to nitrogen metabolism in the sediments and thus affecting the changes in sediment nitrogen [33], and that the physicochemical properties of sediment (particularly the water content) can affect microbial heterotrophic respiration and thus affect the sediment carbon fluxes [34,35]. In summary, vegetation and sediment physicochemical properties influence sediment carbon and nitrogen cycling through the regulation of microbial communities [36].…”
Section: Introductionmentioning
confidence: 99%